The influence of organizational culture and psychosocial safety climate on employee performance through leadership style: Case study at PT PLN (Persero) Project Management Center - Ardian Rizkytama; Rachmawati, Ike Kusdyah (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: The transformation of the global electricity sector requires strong human resource management effectiveness to sustain organizational performance. In Indonesia, PT PLN (Persero) Project Management Center (PUSMANPRO) plays a strategic role in national electricity development. Although organizational achievements show a positive trend, internal performance variations suggest that additional human factors may influence employee performance outcomes. This study examines how corporate culture and psychosocial safety climate affect employee performance, both directly and through leadership style. Background Problems: This study addresses the problem of misalignment between organizational indicators and human resource indicators at PLN PUSMANPRO by exploring the research question: How do corporate culture and psychosocial safety climate influence employee performance directly and indirectly through leadership style? Research Methods: This research applied a quantitative approach with a mediating associative design. Primary data were collected using an online Likert-scale questionnaire from 132 employees, selected through stratified random sampling from a population of 371. Four variables were measured: corporate culture (AKHLAK values), psychosocial safety climate (PSC dimensions), leadership style (four leadership styles), and employee performance (three performance dimensions). Data were analyzed using SEM–PLS to assess structural relationships, including mediation effects. Finding/Results: The results indicate that corporate culture and psychosocial safety climate significantly affect leadership style. Corporate culture and leadership style significantly influence employee performance. However, psychosocial safety climate does not directly influence performance. Leadership style partially mediates the effect of corporate culture and fully mediates the effect of psychosocial safety climate on performance outcomes. Conclusion: Corporate culture is a key determinant of employee performance improvement, and leadership style serves as a crucial linking mechanism between cultural and psychosocial conditions and performance. The findings reinforce theoretical frameworks connecting organizational culture, psychosocial climate, and leadership to performance. Practically, they highlight the need to strengthen work culture and leadership quality to support sustainable performance improvement within PLN PUSMANPRO.